Enhancing direct cytotoxicity and response to immune checkpoint blockade following ionizing radiation with Wee1 kinase inhibition. (2nd November 2019) - Patel, Priya; Sun, Lily; Robbins, Yvette; Clavijo, Paul E.; Friedman, Jay; Silvin, Christopher; Van Waes, Carter; Cook, John; Mitchell, James; Allen, Clint
ABSTRACT: Tumor cells activate the G2/M cell cycle checkpoint in response to ionizing radiation (IR) and effector immune cell-derived granzyme B to facilitate repair and survival. Wee1 kinase inhibition reverses the ability of tumor cells to pause at G2/M. Here, we hypothesized that AZD1775, a small molecule inhibitor of Wee1 kinase, could sensitize tumor cells to IR and T-lymphocyte killing and improve responses to combination IR and programmed death (PD)-axis immune checkpoint blockade (ICB). Multiple models of head and neck carcinoma, lung carcinoma and melanoma were used in vitro and in vivo to explore this hypothesis. AZD1775 reversed G2/M cell cycle checkpoint activation following IR, inducing cell death. Combination IR and AZD1775 induced accumulation of DNA damage in M-phase cells and was rescued with nucleoside supplementation, indicating mitotic catastrophe. Combination treatment enhanced control of syngeneic MOC1 tumors in vivo, and on-target effects of systemic AZD1775 could be localized with targeted IR. Combination treatment enhanced granzyme B-dependent T-lymphocyte killing through reversal of additive G2/M cell cycle block induced by IR and granzyme B. Combination IR and AZ1775-enhanced CD8 + cell-dependent MOC1 tumor growth control and rate of complete rejection of established tumors in the setting of PD-axis ICB. Functional assays demonstrated increased tumor antigen-specific immune responses in sorted T-lymphocytes. The combination of IR and AZD1775 not only lead to enhanced tumor-specific cytotoxicity, it also enhanced susceptibility to T-lymphocyte killing and responses to PD-axis ICB. These data provide the pre-clinical rationale for the combination of these therapies in the clinical trial setting.